2000
DOI: 10.1002/cjce.5450780217
|View full text |Cite
|
Sign up to set email alerts
|

Coal combustion in O2/CO2 mixtures compared with air

Abstract: n 1996, coal was used to generate 25% of the electricity produced worldwide. Because of its large reserves, coal will certainly continue I to play a major role in energy production in North America and worldwide. During the past decade concern has grown about greenhouse gas emissions (CO, , CH, , N, O) and their potential impact on climate change. Since coal-fired power plants account for about 1 1 % of CO, emissions, clean and efficient combustion technologies need to be developed for use in existing and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 2 publications
2
56
0
Order By: Relevance
“…Around mid-1990s, a research consortium led by IHI funded by NEDO did the first pilot scale studies in Japan [11][12][13][14]. During the later part of the 1990s, CANMET [15][16][17] and a research consortium led by Air Liquide [18,19] did further pilot scale studies on this aspect of combustion. Lui et al [20] performed laboratory scale studies on a small downshot reactor firing a bituminous coal in mixtures of O 2 /CO 2 .…”
Section: Previous Research On Oxy-coal Combustion With Recycle Flue Gasmentioning
confidence: 99%
“…Around mid-1990s, a research consortium led by IHI funded by NEDO did the first pilot scale studies in Japan [11][12][13][14]. During the later part of the 1990s, CANMET [15][16][17] and a research consortium led by Air Liquide [18,19] did further pilot scale studies on this aspect of combustion. Lui et al [20] performed laboratory scale studies on a small downshot reactor firing a bituminous coal in mixtures of O 2 /CO 2 .…”
Section: Previous Research On Oxy-coal Combustion With Recycle Flue Gasmentioning
confidence: 99%
“…This reduction is likely due to an increase in the retention of sulphur by ash and the formation of deposits in the furnace due to the recirculation of the flue gas. However, other studies suggest that SO 2 emissions are almost independent of the combustion media [8], being governed only by the oxygen concentration [9] or by the sulphur content of the fuel [10]. Additionally, and due to the accumulation of SO 2 in the system, a higher fraction of SO 2 is oxidized to SO 3 , which can involve serious implications due to corrosion in the boiler and CO 2 transportation systems.…”
Section: Introductionmentioning
confidence: 95%
“…Two main different conclusions were obtained. Some investigators [3][4][5][6] observed that the conversion of sulfur in coal to SO 2 decreased in O 2 /CO 2 combustion compared with traditional air combustion because high SO 3 concentrations in the flue gas during O 2 /CO 2 combustion resulted in sulfur retention by ash or deposits in the furnace. Whereas, Zheng and Furimsky argued that CO 2 plays no insignificant role for the sulfur release compared oxygen by equilibrium calculations [7].…”
Section: Introductionmentioning
confidence: 98%